The effect of learning orientation and business model innovation on entrepreneurial performance: Focused on South Korean start-up companies - Byungyun Bae; Sungyong Choi (Journal of Open Innovation: Technology, Market, and Complexity, 2021)
The purpose of this study is to empirically confirm the importance of learning orientation in the operation of start-up companies. In the literature, it is well known that this learning orientation plays a big role in improving the performance of start-ups by cultivating organizational members' capabilities in detail, encouraging active learning, and creating new knowledge. To this end, a business model innovation framework for start-ups was established by empirically validating the theoretical research model. For the analysis, 139 questionnaires from start-ups with less than 7 years of business history in the incubation center were used. For the novelty of this work, it investigates the causal relationship between the learning orientation of start-ups, business model innovation, and start-up performance (technology acquisition and market expansion). Our research has contributed to the literature on entrepreneurship, innovation and strategy as follows. First, it contributed to the literature on entrepreneurship by redefining the performance of start-up companies as technology acquisition and market expansion through a review of previous studies and providing insight into the importance of learning orientation for start-ups through empirical studies. Second, it contributed to the innovation literature by confirming the importance of business model innovation for start-ups to achieve start-up performance through empirical research. Third, it contributed to the strategic literature by presenting and empirically confirming business model innovation through learning-orientation improvement as a way to achieve the performance of start-up companies.
Keywords: 650; business model innovation; entrepreneurial performance; learning orientation; start-up companies